2016
DOI: 10.1039/c6nr02620f
|View full text |Cite
|
Sign up to set email alerts
|

Core/shell Fe3O4/Gd2O3nanocubes as T1–T2dual modal MRI contrast agents

Abstract: T1-T2 dual modal magnetic resonance imaging (MRI) has attracted considerable interest because it offers complementary diagnostic information, leading to more precise diagnosis. To date, a number of nanostructures have been reported as T1-T2 dual modal MR contrast agents (CAs). However, hybrids of nanocubes with both iron and gadolinium (Gd) elements as T1-T2 dual modal CAs have not been reported. Herein, we report the synthesis of novel core/shell Fe3O4/Gd2O3 nanocubes as T1-T2 dual-modal CAs and their applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 50 publications
3
63
1
Order By: Relevance
“…Therefore, either measured at 1.5 T or 9.4 T, the r 1 values of both GdSalNPs10 and GdSalNPs10‐rBSA5 (ten‐gram‐scale synthesis) are much higher than the commercial Gadavist and Dotarem. The corresponding r 2 / r 1 ratios of GdSalNPs10 and GdSalNPs10‐rBSA5 are lower than 2.0, which are appreciably lower than those of most T 1 MRI contrast agents 21–24. Therefore, the ten‐gram‐scale synthesized GdSalNPs10 and GdSalNPs10‐rBSA5 are both promising T 1 MRI contrast agents by virtue of their very high r 1 values and very low r 2 / r 1 ratios.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, either measured at 1.5 T or 9.4 T, the r 1 values of both GdSalNPs10 and GdSalNPs10‐rBSA5 (ten‐gram‐scale synthesis) are much higher than the commercial Gadavist and Dotarem. The corresponding r 2 / r 1 ratios of GdSalNPs10 and GdSalNPs10‐rBSA5 are lower than 2.0, which are appreciably lower than those of most T 1 MRI contrast agents 21–24. Therefore, the ten‐gram‐scale synthesized GdSalNPs10 and GdSalNPs10‐rBSA5 are both promising T 1 MRI contrast agents by virtue of their very high r 1 values and very low r 2 / r 1 ratios.…”
Section: Resultssupporting
confidence: 60%
“…In this regard, Zhou and co‐workers developed Gd 2 O 3 ‐embedded iron oxide nanoplates with r 1 value of 20.5 m m −1 s −1 and r 2 / r 1 ratio of 7.1 ( B 0 = 3.0 T) 23. Similarly, Li and co‐workers synthesized core‐shell Fe 3 O 4 @Gd 2 O 3 nanocubes whose r 1 value and r 2 / r 1 ratio were 45.24 m m −1 s −1 and 4.1, respectively ( B 0 = 1.5 T) 24. Furthermore, thermal decomposition technique was employed in synthesizing Gd‐doped iron oxide nanoparticles (NPs) with r 1 value of 7.87 m m −1 s −1 and r 2 / r 1 ratio of 23.2 ( B 0 = 9.4 T) 25.…”
Section: Introductionsupporting
confidence: 44%
“…The conjugation of RGD2 resulted in a lower r 1 value and higher r 2 / r 1 ratio, which can be ascribed to the slight aggregation of the nanoparticles induced by RGD2 conjugation. Overall, as measured by a 1.5 T clinical MRI scanner system, the r 1 values of FeGd‐HN3 and FeGd‐HN3‐RGD2 (>70.0 mM −1 s −1 ) are much higher than the reported T 1 ‐weighted MRI contrast agents and Magnevist (a commonly used T 1 ‐weighted MRI contrast agent on the market). The corresponding r 2 / r 1 ratios of FeGd‐HN3 and FeGd‐HN3‐RGD2 (<2.0) are lower than most of the reported T 1 ‐weighted MRI contrast agents and comparable to that of the Magnevist.…”
Section: Methodsmentioning
confidence: 81%
“…The maximum r 1 value was as high as 33.1 mM −1 s −1 , but the corresponding r 2 / r 1 ratio was 8.3 ( B 0 = 4.7 T), which is not low . Li et al reported a synthesis of core–shell Fe 3 O 4 @Gd 2 O 3 nanocubes, whose r 1 value was 45.24 mM −1 s −1 and r 2 / r 1 ratio was 4.1 ( B 0 = 1.5 T) . Yang et al synthesized core–shell nanoparticles of Fe 3 O 4 @SiO 2 and covalently conjugated a Gd chelate (i.e., Gd‐DTPA, DTPA is diethylenetriamine pentaacetic acid) and a RGD peptide (arginine–glycine–aspartic acid) on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is an effective detection method, but its sensitivity is not enough to diagnose tiny tumors . Fluorescence optical imaging (FOI) has high sensitivity and is suitable for visual observation from different levels of living cells to animals, but the disadvantage is the limited depth of penetration and poor spatial resolution .…”
Section: Introductionmentioning
confidence: 99%